Analysis of Irrigation Water Balance in Garum and Jatisari Irrigation Area, Ngajum, Malang Regency - Qomariyah, Dhea Nur; Masitoh, Ferryati (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
The irrigation water requirement must be balanced with the available water to support plant growth and increase agricultural production. Therefore, information regarding the amount of water needed and its availability is essential for irrigation activities. This research analyzed the water flow availability at the Garum DAM intake using the Weibull method, irrigation water requirement in the Garum and Jatisari irrigation areas using Cropwat 8.0 software (Penman-Monteith Method), and water balance between water availability and the irrigation water requirement of the Garum and Jatisari irrigation areas using a comparative method. The data used included intake flow, climate, rainfall, soil, and plant data. The results of this study show that the water flow available at the Garum DAM intake tends to be high in the rainy season and will tend to be lower in the dry season. Furthermore, the water requirement in the Garum and Jatisari irrigation areas tends to be high during the dry season and decreases during the rainy season. The water balance shows that the water available at the Garum DAM intake cannot fulfill the irrigation water requirement of the Garum and Jatisari irrigation areas. This is because of the lack of a water deficit in certain months.